Optimization of a series of potent, selective and orally bioavailable SYK inhibitors. Issue 19 (1st October 2020) - Grimster, Neil P.; Gingipalli, Lakshmaiah; Barlaam, Bernard; Su, Qibin; Zheng, XiaoLan; Watson, David; Wang, Haixia; Simpson, Iain; Pike, Andy; Balazs, Amber; Boiko, Scott; Ikeda, Timothy P.; et al.
Graphical abstract: Abstract: Spleen tyrosine kinase (SYK) is a non-receptor cytosolic kinase. Due to its pivotal role in B cell receptor and Fc-receptor signaling, inhibition of SYK has been targeted in a variety of disease areas. Herein, we report the optimization of a series of potent and selective SYK inhibitors, focusing on improving metabolic stability, pharmacokinetics and hERG inhibition. As a result, we identified 30, which exhibited no hERG activity but unfortunately was poorly absorbed in rats and mice. We also identified a SYK chemical probe, 17, which exhibits excellent potency at SYK, and an adequate rodent PK profile to support in vivo efficacy/PD studies.